Development of Healthcare and Wellness Tourism Marketing - Ordabayeva, Mainur; Yessimzhanova, Saira (International Review of Management and Marketing, 2016)
The present article is concerned with the study of marketing development prospects for tourism organizations and healthcare and wellness tourism companies as a means for creating their competitive advantages at different management levels. The directions for the intensification of healthcare and wellness tourism development in Kazakhstan sanitarium-resort facilities have been substantiated. The review and collation of national and foreign scientists’ works have made it possible to determine the main peculiarities of healthcare and wellness tourism development. The definitions of tourist activities in the area under consideration have been classified. Based on the research carried out on the people, consuming healthcare and wellness services provided by the sanatorium Rakhmanovskiye Kluchi, the preferences of Kazakhstan healthcare and wellness tourism consumers have been analyzed. Moreover, marketing development measures, both for a specific company and tourism organizations and companies of healthcare and wellness area as a whole, have been suggested. Keywords: Healthcare and wellness tourism, wellness, spa, health promoting resources, healthcare and wellness program. Classifications: L83, I19, M31